Central neural activity in rats with tinnitus evaluated with manganese-enhanced magnetic resonance imaging (MEMRI) - Brozoski, Thomas J.; Ciobanu, Luisa; Bauer, Carol A. (Hearing research, 2007)
The pathophysiology of tinnitus, the perception of sound in the absence of acoustic stimulation, is largely unknown, although several lines of research implicate long-term neuroplastic loss of inhibition. The evidence to date suggests that the neuroplastic alterations are likely to be found in multiple brain structures. The present study used manganese-enhanced magnetic resonance imaging (MEMRI) to assess the pattern of neural activity in the central auditory pathway of rats with psychophysical evidence of chronic acoustic-exposure-induced tinnitus. Manganese, an activity-dependent paramagnetic contrast agent, accumulates in active neurons through voltage-gated calcium channels, primarily at synapses, and serves as both a structural and functional indicator. Comparison images were obtained from normal subjects exposed to external tinnitus-like sound, and from tinnitus subjects treated with vigabatrin, a GABA agonist shown to eliminate the psychophysical evidence of tinnitus in rats. MEMRI indicated: (1) In rats with evidence of tinnitus, activity was generally elevated in the auditory brainstem, with significant elevation in the cerebellar paraflocculus, the posterior ventral cochlear nucleus, and the inferior colliculus; in general forebrain structures showed decreased activity, although MEMRI may be a less sensitive indicator of forebrain activity than brainstem activity; (2) in normal rats exposed to a tinnitus-like sound, a similar pattern of elevated brainstem activity and decreased forebrain activity was evident, with the notable exception of the paraflocculus, where artificial tinnitus had no effect and (3) vigabatrin, decreased brainstem activity to control levels, in rats with prior evidence of tinnitus, and decreased forebrain activity to below control levels. It was concluded that chronic tinnitus in rats is associated with focal activity elevation in the auditory brainstem and increased activity in the paraflocculus that may be unique to tinnitus.